Update to the study protocol for a randomized controlled trial comparing mindfulness-based cognitive therapy with maintenance anti-depressant treatment depressive relapse/recurrence: the PREVENT trial. - Kuyken, W; Byford, S; Byng, R; Dalgleish, T; Lewis, G; Taylor, R; Watkins, E; Hayes, R; Lanham, P; Kessler, D; Morant, N; Evans, A (BioMed Central, 2014)
BACKGROUND: Depression is a common and distressing mental health problem that is responsible for significant individual disability and cost to society. Medication and psychological therapies are effective for treating depression and maintenance anti-depressants (m-ADM) can prevent relapse. However, individuals with depression often express a wish for psychological help that can help them recover from depression in the long-term. A recently developed treatment, mindfulness-based cognitive therapy (MBCT), shows potential as a brief group program for people with recurring depression.This trial asks the policy research question; is MBCT with support to taper/discontinue antidepressant medication (MBCT-TS) superior to m-ADM in terms of: a primary outcome of preventing depressive relapse/recurrence over 24 months; and secondary outcomes of (a) depression free days, (b) residual depressive symptoms, (c) antidepressant medication (ADM) usage, (d) psychiatric and medical co-morbidity, (e) quality of life, and (f) cost effectiveness? An explanatory research question also asks whether an increase in mindfulness skills is the key mechanism of change.The design is a single-blind, parallel randomized controlled trial examining MBCT-TS versus m-ADM with an embedded process study. To answer the main policy research question the proposed trial compares MBCT-TS with m-ADM for patients with recurrent depression. Four hundred and twenty patients with recurrent major depressive disorder in full or partial remission will be recruited through primary care. RESULTS: Depressive relapse/recurrence over two years is the primary outcome variable. Analyses will be conducted following CONSORT standards and overseen by the trial's Data Monitoring and Safety Committee. Initial analyses will be conducted on an intention-to-treat basis, with subsequent analyses being per protocol. The explanatory question will be addressed in two mutually informative ways: quantitative measurement of potential mediating variables pre- and post-treatment and a qualitative study of service users' views and experiences. CONCLUSIONS: If the results of our exploratory trial are extended to this definitive trial, MBCT-TS will be established as an alternative approach to maintenance antidepressants for people with a history of recurrent depression. The process studies will provide evidence about the effective components which can be used to improve MBCT and inform theory as well as other therapeutic approaches. TRIAL REGISTRATION: Trial registered 7 May 2009; ISRCTN26666654.